Apoptosis: Mediator molecules, interplay with other cell death processes and therapeutic potentials - Barman J.; Kumar R.; Saha G.; Tiwari K.; Dubey V.K. (My University, 2025)
Apoptosis, a form of programmed cell death, plays a very crucial role in various physiological processes for maintaining cell homeostasis. This process has several characteristic features like membrane blebbing, nuclear condensation, DNA fragmentation and cell shrinkage. Any defect in this highly regulated process eventually leads to extended cell survival and could result in neoplastic cell expansion followed by genetic instability. The apoptotic machinery is mainly processed and regulated by various caspases, a family of cysteine proteases. Significant advancement has been made towards understanding the molecular mechanisms of apoptosis which provides new insights in modulating the life or death of a cell. The main goal of this review is to highlight recent updates on apoptosis, the cross-talk with other cellular death processes and its therapeutic potentials. © 2018 Bentham Science Publishers.